The Influence of Socratic Questioning Technique and Students Critical Thinking toward Their Speaking Competence at SMA Negeri 11 Ambon - Andre Paulus Saleky (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
This study is aimed at 1) describing the students’ speaking competence and 2) students critical thinking skill; 3) finding out the positive and the significant difference in speaking competence between the students who were taught by using Socratic Questioning Technique (SQT) and those who were taught by using Information Gap Technique (IGT); 4) finding out the positive and the significant differences in students speaking competence between those who had high and low critical thinking; and 5) finding out the positive and significant interaction in students speaking competence between teaching techniques and the critical thinking skill. A quasi experiment method (pre-posttest non-equivalent control group design) through the 2 × 2 factorial designs used to represents an independent variable and a dependent variable with different level of thinking. The results showed that there were significantly differences in speaking ability between students who had high critical thinking and those who had low critical thinking. The value of R was 0.840 with interval correlation (0.80 – 1.00) meaning coefficient correlation was very strong and significant in linear regression or gained regression criteria in addition there was a positive and significant interaction in speaking competence between teaching techniques and critical thinking skill.